Effects of Low-Energy Ion Implantation on the Physicochemical Properties of Si Oxides - Allanazarova Sarvinoz Shavkat qizi, Allayarova Gulmira Xolmuratovna (American Journal of Bioscience and Clinical Integrity, 2026)
Thin SiO2 films were obtained by implanting O2+ ions into Si combined with thermal annealing. Oxide films obtained in an UHV setup by thermal oxidation were also used for comparison. Auger electron spectra revealed that these regions contain Si atoms (Figure 2). The degree of coverage of the Si surface with silicon oxide was estimated by the ratio of the area of the Auger peak L23VV of silicon in Si (91 eV) and in SiO2 (76 eV). By varying the ion dose within the range from 8•1015 to 4•1016, the sizes of nanosites can be regulated within the range from 5 – 10 nm to 20 – 25. At D ≤ 8•1016 cm-2, the formation of an island film of SiO2 was observed. Based on experimental studies, it was established that when bombarding SiO2 with Ar+ ions in the surface region of SiO2 at low doses (D ≤5• 1015 cm-2), individual nanocluster regions enriched with up to 50−60 at.%.